Research in History: City, Memory and Architecture - Pérgolis-Valsecchi, Juan Carlos (Corporación Universitaria del Caribe, CECAR., 2020)
Doing research in City and Architecture implies placing yourself in a place and a moment, in the spirit of time of what you want to investigate. This is based on two concepts: the idea of Zeitgeist, that corpus of objects and cultural attitudes that must be observed simultaneously; and the idea of a subject in process. Investigating the history of the City and Architecture is, then, making theory, because one cannot do without the other. From this point of view, we try to observe some referents of the process: Time, as raw material; the Interpretation of Sources; the Space-Place and Memory-History Dichotomies; and Social Representations and Imaginaries. To conclude, pointing out that being objective does not imply being neutral in the face of the events of History, because this way you can access the plurality of meanings of Architecture and the City.